MENTORING CASES OF CHILD SEXUAL ABUSE IN LRC-KJHAM FOR THE PERIOD 2021 – 2023 - Ayu Kurniawati, Citra; Faozi, Safik (Jurnal Meta-Yuridis, 2024)
This Article Explains and analyze the assistance of cases of child sexual violence at LRC-KJHAM for the period 2021 - 2023, the obstacles faced by LRC-KJHAM in efforts to assist victims of child sexual violence and how to overcome them and analyze the fulfillment of the rights of child victims of sexual violence who have been assisted by LRC-KJHAM. The type of research is empirical juridical, examining the applicable legal provisions and what happens in society. In this research, using qualitative methods to provide descriptive data that can be used to write a broad picture of the state of things under study. The data used is primary data refers to information collected directly from the original source, namely interviews with assistants of victims of child sexual abuse and observations at LRC-KJHAM and analyzing Law Number 35 of 2024 Amendments to Law Number 23 of 2002 concerning Child Protection, and Law Number 12 of 2022 concerning Crimes of Sexual Violence. Secondary data obtained from other written sources such as books, scientific journals, archival materials, papers, theses, theses, legal dissertations, and official documents. But in fact, in providing assistance from the start of handling, protecting and recovering victims of child sexual violence, the assistants still experience obstacles and challenges